PENGARUH PENAMBAHAN KACANG MERAH (Phaseolus Vulgaris L.) TERHADAP DAYA TERIMA DAN KANDUNGAN ZAT BESI (Fe) BISKUIT UNTUK WANITA HAMIL - Qudsy, Suci Purnama; Fajri, Roifah; Lisnawati, Naintina (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Background: Prevalence of pregnant women with iron deficiency anemia in Indonesia reach 37.1% in 2013. Consumption of additional food containing iron (Fe) can be prevention alternative for iron deficiency anemia on pregnant women. One of a kind additional food containing iron (Fe) with affordable price is red kidney beans biscuit. Objective: To developt biscuits containing iron (Fe) and find the effects of red beans addition on the acceptance and the iron (Fe) content of biscuit. Method: First stage of this study were the production and formulation of red bean biscuits. The second stage was analysis (acceptability test and iron content test) of selected biscuit from first stage. The study design used a Completely Randomize Design (CRD) with 1 factor and 3 treatments of different red beans addition (20%, 50% and 80%). Results: Red kidney beans addition didn’t have an effect on the flavour (p=0.539) and taste (p=0.237) parameters of biscuits, but had on the colour parameter (p=0.028). Most preferred biscuits color was sample A1 (wheat flour : red bean flour comparison 80% : 20%) with 96.67% panelist like it (29 out of 30 people). Red kidney beans addition had no effect on the iron (Fe) content of biscuit (p=0.368). Conclusion: The addition of red kidney beans didn’t affect on the acceptability, iron content, flavour, and taste parameters, but only had on colour parameter of biscuits.